Exploring AI-Powered Tools for English Learning: Perceptions and Practices of Criminology Students - Sibug, Sheila Marie D.; Pelila, John Rey O.; Tadeo, Gwendolyn S. (Universitas Kapuas, 2025)
Prior research indicates that criminology students have low English proficiency, underscoring the pressing need for effective interventions. Despite the growing use of AI-powered English-language learning aids in education, little is known about how BS Criminology students use, perceive, and manage these technologies. This study fills that knowledge gap. Thus, the paper investigates how 133 second-year BS Criminology students use AI-powered English-learning applications and evaluates the perceived advantages and disadvantages of these tools. A validated survey and semi-structured interviews with purposefully selected participants were used, using a quantitative-descriptive design with simple triangulation. Findings show that the most popular and frequently used tools for improving grammar, writing confidence, and sentence structure were ChatGPT and QuillBot. However, issues with data privacy, over-reliance, and the shallowness of AI interactions in terms of emotion and context were brought out. Although AI technologies offer substantial language support, the study concludes that It should be used in conjunction with human education rather than in place of it. To optimize English language acquisition, educational institutions should implement a blended learning strategy that combines AI tools with supervised human facilitation.